Isolation and characterisation of microorganisms contaminating herbal infusion sold in Minna, Nigeria - Bala, J. D.; Kuta, F. A.; Abioye, O. P.; Adabar, N.U.; Abdulsalam, R.; Adelere, I. A.; Al-Gheethi, Adel A.; Kaizar, H.; Ademujimi, M. M. (Department of Science Education, Federal University of Technology, P. M. B. 65, Minna, Niger State, Nigeria, 2015)
The microbiological assessment of ten herbal infusion samples from ten different locations in Minna, Niger State was investigated. The assessment of the microbial contamination on the herbal products was carried out, using standard methods. Pour plate method was used to cultivate serially diluted portions of the medicinal plant infusion samples. The results revealed that all the herbal preparations had the presence of microbial contaminants. The total heterotrophic counts of the different herbal samples ranged from 0 cfu/mL to 25.0 × 108cfu/mL while the total fungal counts ranged from 3.0×106cfu/mL to 3.5×108cfu/mL. The total viable bacteria counts showed that the highest counts of 25.0 × 108cfu/mL was recorded in the sample from Bosso and the least counts of 0 cfu/mL from Kasuwan-Gwari while the total fungal counts showed that the highest count of 3.5×108cfu/mL was found in the sample obtained from FUT campus and the least counts of 3.0×106cfu/mL in the sample from Mai-Kunkele. One way analysis of variance (ANOVA) showed that there was significant difference (p<0.05) in the microbial load of the herbal infusions from each location. The microbial isolates identified were E. coli, Staphylococcus aureus, Shigella sp, Klebsiella sp, Pseudomonas sp, Micrococcus sp, Salmonella sp, Aspergillus sp, Penicillium sp and Saccharomyces cerevisaie. Members of the genus Aspergillus were found to be predominant. This suggests that the herbal infusion harbors microorganisms that could be hazardous to human health and hence producers should maintain the highest possible level of hygiene during the processing and packaging of the products in order to ensure safety of the products.